SPLINE FINITE DIFFERENCE METHOD FOR A CLASS OF BOUNDARY-VALUE PROBLEMS - I. Khan; T. Aziz; A. Khan; S. M. El-Sayed (Journal of the Indonesian Mathematical Society, 2008)
"Pdf file"DOI : http://dx.doi.org/10.22342/jims.14.1.63.57-62